2020
DOI: 10.1101/2020.03.09.984716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The demographic decline of a sea lion population followed multi-decadal sea surface warming

Abstract: 9Background: The population growth of top predators depends largely on environmental 2 0 3 1 year mean of 22.24°C.3 2 Conclusions: The negative relation of the population size with warming sea surface conditions 3 3was evident, and the predictability of the former from the sea surface temperature 100-year 3 4 2 anomalies was high. The mechanistic links of this relation are still untested, but an apparent 3 5 diversification of pelagic fish catches suggests a reduction of high quality prey. We propose that this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In the central region, the growth rate has remained relatively low (1%) and the decline has been continuous since 1978, reducing the population to a level that may represent a threat to the species’ persistence. Not all reproductive colonies were included in our analysis; however, previous studies examining all colonies have reported the same trend (Szteren, Aurioles‐Gamboa & Gerber, 2006; Adame et al, 2020). Meanwhile, the population in the southern region increased steadily during the same period.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the central region, the growth rate has remained relatively low (1%) and the decline has been continuous since 1978, reducing the population to a level that may represent a threat to the species’ persistence. Not all reproductive colonies were included in our analysis; however, previous studies examining all colonies have reported the same trend (Szteren, Aurioles‐Gamboa & Gerber, 2006; Adame et al, 2020). Meanwhile, the population in the southern region increased steadily during the same period.…”
Section: Discussionmentioning
confidence: 91%
“…Considering the climatology of the entire GoC for the period from 1920 to 2018, Adame et al (2020) argue that positive SST anomalies began to be registered around 1990, about the same time that the California sea lion population in the GoC began to decrease. They propose that the increase in the SST has resulted in a diversification of pelagic fish catches by fisheries, which suggests a reduction in high‐quality prey for California sea lions.…”
Section: Discussionmentioning
confidence: 99%
“…Although otariid reproductive males do not forage during the reproductive season, they require sufficient accumulation of fat stores before the season to energetically sustain this stressful period ( Campagna et al 1988 ; Pavés et al 2005 ). Therefore, adverse environmental conditions associated with higher SST and decline in prey items could lead to poor storage of fat reserves and early departure of males from reproductive colonies ( Sydeman and Allen 1999 ; Adame et al 2020 ). This reduction in reproductive male density could potentially facilitate intromission of SASL into the fur seal colony, increasing the number of agonistic interactions.…”
Section: Discussionmentioning
confidence: 99%